Peningkatan Produksi UMKM Sebagai Upaya Pemberdayaan Ekonomi Umat di Ponorogo dalam Perspektif Ekonomi Islam: (Increasing Production of MSMEs as an Effort to Empower the People's Economy in Ponorogo in the Perspective of Islamic Economics) - Syafa Tasya Wahyuleananda; Amin Wahyudi (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
This research aims to find out and analyze how to increase the production of MSME owners in Ponorogo, which is an effort to empower the people's economy. Researchers use qualitative methods. Where this research uses context to explain phenomena, its analysis requires the use of critical thinking. Data sources are obtained from observations, interviews, literature and appropriate journals to guarantee the accuracy of research results. The results of this research are in increasing the production of food & beverage MSME owners in Ponorogo, most of whom are Muslims, who have been able to implement production processes that are in accordance with Islamic economics. MSME owners have indirectly fulfilled two goals in the production process, namely individual self-sufficiency and also the surrounding community. Empowerment of food & beverage MSMEs in Ponorogo is seen from three dimensions, namely the initial stage which is carried out by building a favorable environment where potential communities can develop with new innovations that are created by business owners. Furthermore, in terms of strengthening empowered communities, chicken & duck food & beverage business owners are still self-taught. Meanwhile, in terms of financial support, it is very helpful for the community to be empowered and can be relied on by the community if at any time they need emergency funds. By assessing these three dimensions, empowering the people from increasing the production of duck & chicken food & beverage MSMEs in Ponorogo is very beneficial and able to make individuals and the surrounding community develop.